How customers perceived cost, perceived value and self-efficacy influence the broadband adoption intention in telecommunication industries / Nor Hafidzah Zakaria - Zakaria, Nor Hafidzah (2012)
The aim of this study was to examine the customers perceived cost, perceived value and self-efficacy influence broadband adoption intention in telecommunication industries. There are 3 factors that been studied, which were perceived cost, perceived value and self- efficacy. This study also was conduct to identify what are the most preferred factors that influence broadband adoption intention in telecommunication industries. Questionnaire had been used in order to get feedback and opinion from customers. Researcher had distributed 100 questionnaires to broadband users in Kota Bharu area. From data collected and analysed shows that self efficacy is the most important factor contribute to broadband adoption intention. Second important factor is perceived value and the perceived cost shows not significant result or can be explained as factors that did not contribute to customer adoption of broadband. From result obtained, the researcher made some recommendation to the industries in order to increase broadband adoption intention